Light-mediated activation reveals a key role for Rac in collective guidance of cell movement in vivo. - Wang, X.; He, L.; Wu, Y.I.; Hahn, K.M.; Montell, D.J. (Nature Cell Biology, 2010)
The small GTPase Rac induces actin polymerization, membrane ruffling and focal contact formation in cultured single cells but can either repress or stimulate motility in epithelial cells depending on the conditions. The role of Rac in collective epithelial cell movements in vivo, which are important for both morphogenesis and metastasis, is therefore difficult to predict. Recently, photoactivatable analogues of Rac (PA-Rac) have been developed, allowing rapid and reversible activation or inactivation of Rac using light. In cultured single cells, light-activated Rac leads to focal membrane ruffling, protrusion and migration. Here we show that focal activation of Rac is also sufficient to polarize an entire group of cells in vivo, specifically the border cells of the Drosophila ovary. Moreover, activation or inactivation of Rac in one cell of the cluster caused a dramatic response in the other cells, suggesting that the cells sense direction as a group according to relative levels of Rac activity. Communication between cells of the cluster required Jun amino-terminal kinase (JNK) but not guidance receptor signalling. These studies further show that photoactivatable proteins are effective tools in vivo.